Effect of IL-6 and hsCRP Serum Levels on Functional Prognosis in Stroke Patients Undergoing IV-Thrombolysis: Retrospective Analysis - Pawluk H (Dove Medical Press, 2020)
Hanna Pawluk,1 Grzegorz Grześk,2 Renata Kołodziejska,1 Mariusz Kozakiewicz,3 Alina Woźniak,1 Elżbieta Grzechowiak,4 Maciej Szumny,4 Piotr Sobolewski,5 Leszek Bieniaszewski,6 Grzegorz Kozera6 1Department of Medical Biology and Biochemistry, Faculty of Medicine, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Bydgoszcz, Poland; 2Department of Cardiology and Clinical Pharmacology, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Bydgoszcz, Poland; 3Department of Geriatrics, Division of Biochemistry and Biogerontology, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Bydgoszcz, Poland; 4Department of Neurology, Faculty of Medicine, Collegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Bydgoszcz, Poland; 5Department of Neurology and Stroke Unit, Holy Spirit Specialist Hospital in Sandomierz, Jan Kochanowski University, Kielce, Poland; 6Medical Stimulation Center, Medical University of Gdańsk, Gdańsk, PolandCorrespondence: Hanna Pawluk Department of Medical Biology and Biochemistry, Faculty of MedicineCollegium Medicum in Bydgoszcz, Nicolaus Copernicus University in Toruń, Karłowicza 24, Bydgoszcz 85– 092, PolandTel +48 52 585 37 55Email hannapawluk1@wp.plPurpose: We evaluated the relationship between pretreatment IL-6 and hsCRP levels, symptom severity and functional outcome of patients with acute ischemic stroke (AIS) treated with IV-thrombolysis.Patients and Methods: IL-6 and hsCRP samples were obtained from 83 consecutively treated Caucasian patients with AIS prior to initiation of IV-thrombolysis. Severity of stroke symptoms was assessed using the National Institutes of Health Stroke Scale (NIHSS), whereas functional outcome was assessed with modified Rankin Scale (mRS). The commercially available sets of enzymatic immune tests were used to estimate the concentrations of inflammatory markers in serum.Results: Medians of IL-6 serum concentrations prior to IV-thrombolysis were lower in patients with favorable (mRS 0– 2 pts) functional outcome than in those with unfavorable (mRS 3– 6 pts) functional outcome, both at hospital dismission (5.92: 2.30– 7.71 vs 9.46: 3.79– 17.29 pg/mL; p< 0.01) and on the ninetieth day from stroke onset (5.87: 2.30– 10.58 vs 10.9: 5.94– 17.28 pg/mL; p< 0.01). There were no existing differences regarding hsCRP levels between groups (2.49: 0.11– 9.82 vs 4.44: 0.32– 9.87 mg/dL; p=0.30 and 2.57: 0.11– 2.57 vs 2.83: 0.32– 9.32 mg/dL; p=0.75, respectively). Patients with lacunar strokes were characterized by lower median of IL-6 (5.96: 2.87– 13.0% vs 7.29: 2.30– 17.28; p=< 0.02) and hsCRP (2.25: 0.11– 9.82 vs 4.84: 0.35– 9.87; p=0.01) than those with nonlacunar infarctions. Multivariate analysis showed an impact of IL-6 on mRS measured on hospital dismission and after three months, regardless of their initial NIHSS, presence of hemorrhagic transformation and type 2 diabetes. No impact of hsCRP, lacunar etiology and patients’ age on functional outcome existed.Conclusion: Regardless of the stroke etiology, pretreatment of IL-6, but not of hsCRP levels, may help to predict functional outcome after IV-thrombolysis independently of symptom severity and stroke complications.Keywords: inflammatory markers, ischemic stroke, thrombolysis, old age diseases